Fall frequency and associated factors among men and women with or at risk for HIV infection1. Issue 10 (November 2016) - Erlandson, KM; Plankey, MW; Springer, G; Cohen, HS; Cox, C; Hoffman, HJ; Yin, MT; Brown, TT
Abstract : Objectives: Falls and fall‐related injuries are a major public health concern. HIV‐infected adults have been shown to have a high incidence of falls. Identification of major risk factors for falls that are unique to HIV infection or similar to those in the general population will inform development of future interventions for fall prevention. Methods: HIV‐infected and uninfected men and women participating in the Hearing and Balance Substudy of the Multicenter AIDS Cohort Study and Women's Interagency HIV Study were asked about balance symptoms and falls during the prior 12 months. Falls were categorized as 0, 1, or ≥ 2; proportional odds logistic regression models were used to investigate relationships between falls and demographic and clinical variables and multivariable models were created. Results: Twenty‐four per cent of 303 HIV‐infected participants reported at least one fall compared with 18% of 233 HIV‐uninfected participants ( P = 0.27). HIV‐infected participants were demographically different from HIV‐uninfected participants, and were more likely to report clinical imbalance symptoms ( P ≤ 0.035). In univariate analyses, more falls were associated with hepatitis C, female sex, obesity, smoking, and clinical imbalance symptoms, but not age, HIV serostatus or other comorbidities. In multivariable analyses, female sex and imbalance symptoms were independently associated with more falls. Among HIV‐infected participants, smoking, a higher number of medications, and imbalance symptoms remained independent fall predictors, while current protease inhibitor use was protective. Conclusions: Similar rates of falls among HIV‐infected and uninfected participants were largely explained by a high prevalence of imbalance symptoms. Routine assessment of falls and dizziness/imbalance symptoms should be considered, with interventions targeted at reducing symptomatology.